Sistema fibrinolítico: uso de varfarina versus rivaroxaban em pacientes com fibrilação atrial - Priscila Samara Sergio Moreira (2015)
Atrial fibrillation (AF), an arrhythmia with hemostatic system changes, is a risk factor for the occurrence of stroke. Traditionally, the most effective therapy in the prevention of stroke in such patients has been oral anticoagulation with vitamin K inhibitors, particularly warfarin, whose disadvantages and adverse effects have led to their replacement by "direct oral anticoagulants", as factor X inhibitor. This preliminary study aims to conduct a comparative approach between the hemostatic effects of warfarin and rivaroxaban, a direct factor Xa inhibitor, on the fibrinolytic system. We studied patients with AF distributed into two groups, namely, patients using either warfarin (n = 12) or rivaroxaban (n = 28), and a control group (n = 18). Hemostatic parameters studied were PT / INR, fibrinogen, F1 + 2, D-dimer, t-PA, TAFI and PAI-1. The PT / INR had higher results for both patient groups compared to the control group. Contrary to the F1 + 2, patients using both oral anticoagulants showed reduced levels compared to the control, and the use of warfarin had the lowest values. For TAFI, patients on warfarin use or rivaroxaban showed higher values compared to the control group. Among the three groups there was no difference for the fibrinogen, D-dimer, t-PA and PAI-1. The data taken together lead to the conclusion that the use of direct oral anticoagulant (anti-factor Xa) decreased the F1 + 2 levels, indicating lower generation of thrombin in vivo, prolonging the TP and increasing INR, but in a less sharp way compared to the use of the traditional warfarin. Concerning to the fibrinolytic system, TAFI was the only parameter showing difference between groups, with higher levels in the groups under warfarin or rivaroxaban treatment compared to the control. A data analysis, as a function of time, between rivaroxaban administration and blood collection, revealed that only the PT / INR suffer greater effect up to 12 hours after the drug intake, dropping to levels close to normal in the subsequent hours before next dose. This finding reinforces the potential of TP to monitor use of rivaroxaban in exceptional or high-risk situations.